2023
DOI: 10.1111/clr.14204
|View full text |Cite
|
Sign up to set email alerts
|

Ridge preservation in periodontally compromised molar sockets with and without primary wound closure: A comparative controlled clinical trial

Yiping Wei,
Liping Zhao,
Haoyun Zhang
et al.

Abstract: ObjectiveThis study aimed to compare hard‐ and soft‐tissue changes after ridge preservation in periodontally compromised molar sockets with and without primary wound closure.Materials and MethodsForty molars with severe periodontitis requiring extraction were included and allocated to two treatment modalities. After tooth extraction, the sockets were filled with deproteinized bovine bone mineral and covered with a bioabsorbable porcine collagen membrane. Primary wound closure was achieved in the control group,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Similarly, Tadinada et al [ 21 ] demonstrated a significantly thinner alveolar bone on the impacted side at a depth of 2 mm and no significant difference in the depth of 6 mm; nevertheless, unlike our study, the thickness was significantly lower on the impacted side compared to the non-impacted side at a depth of 10 mm. It should be noted that the alveolar ridge resorption happens in a specific location in the absence of a specific tooth (extraction or impaction), and compared to vertical bone reduction, the amount of bone resorption is greater in the horizontal direction, which affects the thickness of the bone [ 28 , 29 ]. Thus, greater thickness on the impacted side in the present study can be explained by the possibility that the impacted teeth are closer to the ridge.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Tadinada et al [ 21 ] demonstrated a significantly thinner alveolar bone on the impacted side at a depth of 2 mm and no significant difference in the depth of 6 mm; nevertheless, unlike our study, the thickness was significantly lower on the impacted side compared to the non-impacted side at a depth of 10 mm. It should be noted that the alveolar ridge resorption happens in a specific location in the absence of a specific tooth (extraction or impaction), and compared to vertical bone reduction, the amount of bone resorption is greater in the horizontal direction, which affects the thickness of the bone [ 28 , 29 ]. Thus, greater thickness on the impacted side in the present study can be explained by the possibility that the impacted teeth are closer to the ridge.…”
Section: Discussionmentioning
confidence: 99%